Self-driving dynamic plasmonic colors based on needle steering for simultaneous control of transition direction and time on metallic nanogroove metasurfaces. Issue 43 (3rd November 2021) - He, Xiaoping; Li, Guozhou; Wu, Dong
Abstract : The direction-controllable and fast color transition is achieved simultaneously by utilizing a needle to direct the flow of water and gas pressure to drive water. The transition time is minimal for the metal materials so far. Abstract : Dynamically tunable plasmonic colors hold great promise for a wide range of applications including color displays, colorimetric sensing, and information encryption. However, dynamic control speed of plasmonic colors is still slow to date. Herein, we propose to use a needle to direct the flow of water and gas pressure to drive water, realizing a simultaneous direction-controllable and fast plasmonic color transition. The highly reflected background light of the metallic nanogroove metasurface is suppressed to generate high-purity plasmonic colors through the cross-polarized input and output configuration. When the environment is changed from air to water, a giant color change from cyan to red (a wavelength shift of 156 nm) is experimentally observed. More importantly, by utilizing a needle to steer the flow of water, direction-controllable and fast plasmonic color transition is achieved by controlling gas pressure to drive water. Compared with current state-of-the-art plasmonic color scanning technology, the color transition time via water driven by gas pressure decreases by three orders of magnitude for the same scanning length. The multi-degrees of freedom dynamic structural colors could have potential applications in dynamic displays, anti-counterfeiting, and information security.